2018
DOI: 10.3847/1538-3881/aab70d
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Parameters and Radial Velocities of Hot Stars in the Carina Nebula

Abstract: The Carina Nebula is an active star forming region in the southern sky that is of particular interest due to the presence of a large number of massive stars in a wide array of evolutionary stages. Here we present the results of the spectroscopic analysis of 82 B-type stars and 33 O-type stars that were observed in 2013 and 2014. For 82 B-type stars without line blending, we fit model spectra from the Tlusty BSTAR2006 grid to the observed profiles of Hγ and He λλ 4026, 4388, and 4471 to measure the effective te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…We studied the internal structure and kinematics of the two OB associations Cyg OB2 and Car OB1 in the Galaxy using the high-precision astrometric data from Gaia DR2 (Gaia Collaboration et al 2018) and RVs from previous studies (Kiminki et al 2007;Damiani et al 2017;Hanes et al 2018). From the distribution of distances, we concluded that these associations are genuine structures rather than a line-ofsight coincidence of several stellar groups.…”
Section: Discussionmentioning
confidence: 92%
“…We studied the internal structure and kinematics of the two OB associations Cyg OB2 and Car OB1 in the Galaxy using the high-precision astrometric data from Gaia DR2 (Gaia Collaboration et al 2018) and RVs from previous studies (Kiminki et al 2007;Damiani et al 2017;Hanes et al 2018). From the distribution of distances, we concluded that these associations are genuine structures rather than a line-ofsight coincidence of several stellar groups.…”
Section: Discussionmentioning
confidence: 92%
“…the mean of the intensity weighted velocity map of the pillar). Plotted on the same colour scale are the radial velocities of the surrounding O stars taken from the 2014 epoch measurements of Hanes et al (2018), and Table 2 of Kiminki & Smith (2018), where the colour reflects the mean measured radial velocity for each star. The radial velocities of the stars are plotted on the same colour scale as the CO to highlight which ones are more likely to be influencing the observed molecular gas (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The pillars sample the 'Southern Pillars', 'Northern Pillars', and the 'Southwestern Pillars' complexes as defined in Hartigan et al (2015), and in the following we use their pillar Table 4 of Hanes et al (2018) and Table 2 of Kiminki & Smith (2018). The colours of the star markers corresponds to their radial velocities of those stars.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Carina Nebula, at a distance of ≈ 2.3 kpc (see Smith & Brooks 2008, for a review), is one of the most massive and active star forming regions in our Galaxy and harbors a large population of high-mass stars (M ≥ 8 M ). With 70 optically identified O-type stars, three known Wolf-Rayet (WR) stars, and η Car with its companion (see Smith 2006;Alexander et al 2016;Hanes et al 2018), the currently known population comprises 75 stars with masses above 18 M . These massive stars constitute a large OB association, in which Tr 14, 15, and 16 are the most prominent open clusters in optical images.…”
Section: Introductionmentioning
confidence: 99%